Differential expression of heat shock proteins in tissues of riverine buffaloes - SODHI, MONIKA; KISHORE, A; SHARMA, A; SHANDILYA, U K; KUMARI, P; MUKESH, MANISHI (The Indian Journal of Animal Sciences, 2015)
In this study, an effort was made to study tissue-specific expression of some of the major heat shock protein (HSP) genes in riverine buffaloes. Samples (30) comprising 5 each of kidney, liver, muscle, heart, mammary gland and PBMCs were utilized for expression analysis under no heat shock condition. Amongst HSPs, HSP27 mRNA showed maximum expression in all the analyzed 5 tissues, viz. heart, kidney, liver, muscle and mammary gland, indicating this to be the most abundant form. However, in comparisons to tissues, HSP27 expression was low in PBMCs. On the other hand, HSP40 transcript was expressed at higher level in PBMCs while HSP60 and HSP90 transcripts were found highly expressed in mammary gland. The expression of HSP70 mRNA was highest in muscle, however HSP70 mRNA level was prominently high in all other tissues. The study helped to generate base line expression data on major HSP genes in different buffalo tissues. In future, the information presented here would be useful in evaluating the tissue specific response to any physiological and thermal stressors in buffaloes.